Impact of the supervision in the improvement of the quality of the management of the Cusco-Peru region - Zúñiga Alvárez, Luis (Avances en Supervisión Educativa, 2008)
This article is a synthesis of the major report Educational Supervision carried out by Educational Local Management Units in Secondary Education Schools in the Region of Cusco (Peru): A perception of Educational Agents, a thesis applied to obtain the Magister Degree on Educational Sciences with a mention on Educational Administration at the Pontifical Catholic University in Chile. The study has as a general aim to describe the functions that take priority in the supervision carried out by the Educational Local Management Units in secondary education state schools in the region of Cusco, Peru, from the point of view teachers, headmasters and experts on secondary education.